2017
DOI: 10.5098/hmt.8.37
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady MHD Three-Dimensional Casson Nanofluid Flow Over a Porous Linear Stretching Sheet With Slip Condition

Abstract: In this paper we study the effects of thermal radiation, heat and mass transfer on the unsteady magnetohydrodynamic(MHD) flow of a three dimensional Casson nanofluid. The flow is subject to partial slip and convective conditions. The traditional model which includes the effects of Brownian motion and thermophoresis is revised so that the nanofluid particle volume fraction on the boundary is not actively controlled. In this respect the problem is more realistic. The dimensionless governing equations were solved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 15 publications
4
6
0
Order By: Relevance
“…Moreover, the numerical findings are presented quite clearly in the form of various graphical and tabular illustrations. These results are discussed thoroughly in terms of velocity, temperature, and concentration profiles and validated accurately by comparing our tabular results with those obtained previously by the spectral quasilinearization method (Oyelakin et al 46 ) and currently by RKFM integrated with shooting technique (ST) as revealed in the validation section. Furthermore, the salient features of the present investigation are also clinched.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…Moreover, the numerical findings are presented quite clearly in the form of various graphical and tabular illustrations. These results are discussed thoroughly in terms of velocity, temperature, and concentration profiles and validated accurately by comparing our tabular results with those obtained previously by the spectral quasilinearization method (Oyelakin et al 46 ) and currently by RKFM integrated with shooting technique (ST) as revealed in the validation section. Furthermore, the salient features of the present investigation are also clinched.…”
supporting
confidence: 80%
“…For simplifying the mathematical complexity of the studied flow model, the resulting partial differential equations described by Equations ( 1)-( 5) are converted into a nonlinear coupled dimensionless system of ordinary differential equations (ODEs). According to Oyelakin et al, 46 this transformation can be realized with the aid of the following feasible conversions.…”
Section: Mathematical Formulationmentioning
confidence: 99%
“…The principal equations for mass, momentum, and energy conservations with nanoparticle concentration using above considerations can be composed as: (see Refs. [22,29,30]…”
Section: Modelingmentioning
confidence: 99%
“…Hussain et al [21] explored the series solution of Casson nanoliquid flow owing to linearly stretchable surface under viscous dissipation effect. More studies are carried out for Casson nanoliquid flow due to stretchable surface by many researchers [22][23][24][25][26][27], under the influences of various mechanisms like: Joule heating, porous medium, convective heat transport, hydromagnetic flow, slip conditions, thermal radiation, inclined surface, etc. Chamkha et al [28] discussed the similarity solution for unsteady nanofluid flow because of moveable surface in the expanse of boundary layer, under the inspiration of chemical reaction through porous media with suction/injection parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Bhattacharyya (2013) examined boundary layer stagnationpoint flow of Casson fluid and heat transfer towards a shrinking/stretching sheet is studied. Recently, Oyelakin et al (2017) studied the effects of thermal radiation, heat and mass transfer on the unsteady magnetohydrodynamic(MHD) flow of a three dimensional Casson nanofluid using the spectral quasi-linearisation method. The partial differential equations governing the unsteady MHD flow on a rotating cone in a rotating fluid were solved by Roy et al (1998), asymptotic solutions were presented for large magnetic parameter M .…”
Section: Introductionmentioning
confidence: 99%